Polymicrobial empyema; a novel case of Actinomyces turicensis. (2021) - Johnson, Shelsey W.; Billatos, Ehab
Abstract: Empyema or infection of the pleural space is a well described complication of pneumonia, however knowledge of culprit pathogens is still evolving. We report a novel case of empyema due to Actinomyces turicensis, a commensal of the oropharynx and female urogenital tract but previously undescribed cause of empyema . We additionally review general pathogenesis of Actinomyces species within the pleural space. Familiarity with this unique pleural infection pathogen is important for selection of adequate antimicrobial therapy given the propensity of anaerobes such as Actinomyces species to disobey anatomic boundaries and recrudescence of infection in the absence of appropriate therapy.